Electrochemical synthesis and corrosion protection properties of poly(o-toluidine) coatings on low carbon steel - Shinde, V.; Sainkar, S. R.; Patil, P. P. (Journal of Applied Polymer Science, 2005)
Uniform and strongly adherent poly(o-toluidine) (POT) coatings have been synthesized on low carbon steel (LCS) substrates by electrochemical polymerization (ECP) of o-toluidine under cyclic voltammetric conditions from an aqueous sodium tartrate solution. Cyclic voltammetry (CV), UV-visible absorption spectroscopy, Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) measurements, and scanning electron microscopy (SEM) were used to characterize these coatings, which indicates that the sodium tartrate is a suitable medium for the ECP of o-toluidine and it occurs without noticeable dissolution of LCS. Corrosion protection properties of the POT coatings were evaluated in aqueous 3% NaCl by the potentiodynamic polarization measurements and CV. The result of the potentiodynamic polarization demonstrates that the POT coating has ability to protect the LCS against corrosion. The corrosion potential was about 334 mV more positive in aqueous 3% NaCl for the POT-coated LCS than that of bare LCS and reduces the corrosion rate of LCS almost by a factor of 50. (c) 2005 Wiley Periodicals, Inc.
Keywords: conducting polymers; Corrosion resistant coatings; cyclic voltarnmetry; Electrochemical polymerization; FT-IR; Poly(o-toluidine); UV-vis spectroscopy

Main chain thermotropic liquid crystalline polyurethanes containing biphenyl mesogens based on novel AB-type self-polycondensation route: FT-IR and XRD studies - Ranganathan, T.; Gowd, E. B.; Ramesh, C.; Kumar, Anil (Journal of Polymer Science Part A-Polymer Chemistry, 2005)
The detailed mesophasic characterization of main chain liquid crystalline polyurethanes containing biphenyl mesogen, which were synthesized by the novel AB-type self-polycondensation approach, was carried out by using Differential Scanning Calorimetry (DSC), Polarized Optical Microscopy (POM), variable temperature X-ray Diffraction (XRD), and Fourier Transform Infrared (FT-IR) spectroscopic studies. The type of mesophase present in these polymers was identified to be the smectic A phase by POM and XRD studies. The smectic layer thickness was found to increase as the length of the spacer increased. The effect of temperature on the hydrogen bonding was analyzed by FT-IR studies. The curve-fitting analysis of the NH stretching and C=O stretching modes of vibrations indicated a gradual decrease in hydrogen bonding during the transition from the crystalline state to the mesophase. The mesophase to isotropic liquid transition was then accompanied by the complete disappearance of the hydrogen bonding. The biphenyl bands also showed changes during phase transitions due to the coupling of biphenyl vibration modes with the urethane linkage attached to it. (c) 2005 Wiley Periodicals, Inc.
Keywords: FT-IR; liquid-crystalline polymers; polyurethanes; XRD studies

Poly(acrylonitrile) ultrafiltration membranes. I. polymer-salt-solvent interactions - Phadke, M. A.; Musale, D. A.; Kulkarni, Sudhir S.; Karode, Sandeep K. (Journal of Polymer Science Part B: Polymer Physics, 2005)
Fourier transform infrared spectroscopy was used to study the interactions among LiCl, ZnCl2, and AlCl3 with NN-dimethylformamide (DMF) and poly (acrylonitrile) (PAN). It was observed that all three salts complex with DMF as well as PAN. The strength of the cation interaction with the > C=O oxygen of DMF was found to be higher than that with the -CN group of PAN. The > C=O stretching frequency of DMF with ZnCl2 was red shifted, indicating stronger complex formation compared with other two cations. With the addition of salt, the salt-DMF pseudo solvent was found to become a 0 solvent for PAN compared with neat DMF. This change in PAN solvation power was primarily the result of DMF-salt complexation. As a result of the complexation, Mark-Houwink constant a, was found to reduce from 0.75 (for pure DMF) to similar to 0.6 for DMF-salt solvents, indicating decreased PAN chain expansion. Comparison of intrinsic viscosity [n] values indicated that addition of salts to PAN-DMF solutions resulted in: (i) decrease in the DMF solvation. power, which causes less expanded polymer coils, and (ii) increased interpolymer chain entanglements via salt-promoted chain association. (c) 2005 Wiley Periodicals, Inc.
Keywords: activation energy viscosity; Additives; FT-IR; Poly(acrylonitrile); solution properties

Synthesis of high silica content silicoaluminophosphate-5 (SAPO-5) from non-aqueous medium using hexamethyleneimine template - Venkatathri, N (Journal of Scientific & Industrial Research, 2005)
Silicoaluminophosphate-5 (SAPO-5) molecular sieve with up to 2.4 Si atom per unit cell have been synthesized using hexamethyleneimine template in ethylene glycol medium (molar ratio of silica in the reaction gels up to 0.3). Crystallinity and silicon incorporation are confirmed by XRD, XRF, N, sorption study, TG/DTA, SEM. pyridine TPD technique and hydroxyl region FT-IR. These materials with high Si concentration show higher activity for toluene alkylation reaction than samples prepared with up to 0.1 molar ratio of silica in the gel of aqueous media.
Keywords: aqueous; FT-IR; hydroxyl region; non-aqueous; SAPO-5; SEM; TG/DTA; XRD

Synthesis and characterization of high silica content silicoaluminophosphate SAPO-35 from non-aqueous medium - Venkatathri, N. (Catalysis Communications, 2006)
SAPO-35 with up to 15.6 Si atoms per unit cell have been synthesized, using hexamethyleneimine as template in ethylene glycol medium (molar ratio of silica in the reaction gets up to 2.5). Crystallinity and silicon incorporation was confirmed by XRD, XRF, TG/DTA, SEM, FT-IR and Al-27 and Si-29 MASNMR. These SAPO-35 materials with high Si concentration show higher activity for methanol to olefin reaction than samples prepared with up to 0.3 molar ratio of silica in the get. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: ammonia adsorption; FT-IR; MASNMR; methanol to olefin; non-aqueous medium; SAPO-35; SEM; TG/DTA; XRD

Synthesis and characterization of TAPO-31 molecular sieves using tripropylamine template - Venkatathri, N.; Shetty, V. N. (Catalysis Communications, 2006)
TAPO-31 was synthesized hydrothermally using a novel template tri-n-propylamine for the first time. C and N analysis shows the butanol from titanium tetrabutoxide plays an important role in the synthesis. The incorporation of titanium into framework of phosphorous and both aluminiurn and phosphorous sites was suggested from elemental analysis. Isomorphous substitution of titanium (III) in AlPO framework was confirmed from ESR and (31)p MASNMR spectra. UV-Vis and XPS spectra revealed a partial oxidation of framework titanium (III) into titanium (IV) in the calcined TAPO-31 and thus the presence of redox centers in the products. The higher titanium content (Al/Ti = 10) TAPO-31 sample shows higher activity for phenol hydroxylation compared to lower titanium content (Al/Ti = 20) and Titanium impregnated AIPO(4)-31. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: ESR; FT-IR; MASNMR; SEM; TAPO-31; TG/DTA; tripropylamine; UV-Vis; XPS; XRD

Synthesis, characterization and catalytic properties of vanadium aluminophosphate molecular sieves VAPO-31 and VAPSO-Amr from non-aqueous media - Venkatathri, N. (Applied Catalysis A-General, 2006)
Vanadium samples containing aluminophosphate molecular sieve (VAPO-31) and amorphous vanadium silicoaluminophosphate (VAPSO-Amr) have been synthesized using hexamethyleneimine template from non-aqueous media for the first time. XRD and SEM analyses confirm the phase purity of the synthesized samples. FT-IR analysis suggests the incorporation of V4+ in the aluminophosphate framework. ESR, UV-vis spectroscopic, and XPS techniques and cyclicvoltametric studies confirm the incorporation of vanadium and reveal its presence in tetrahedral and square pyramidal environments in the as-synthesized samples. Cyclic voltammetry reveals the presence of two redox couples in VAPO-31. This catalyst is found to be a good oxidation catalyst. Although most of the properties of VAPO-31NA and VAPSO-Amr are similar, the latter can access more vanadium and V4+ ions. Compared to aqueous media samples, it can incorporate more vanadium especially V5+, ions and has been found to be better oxidation catalyst. The physicochemical properties also change with media. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: cyclic voltammetry; ESR; FT-IR; MAS NMR; non-aqueous; SEM; TG/DTA; UV-Vis; VAPO-31; XPS; XRD

Growth of barium oxalate crystals in agar-agar gel and their characterization - Dalai, P. V.; Saraf, K. B.; Shah, S. (Crystal Research and Technology, 2009)
{Single crystals of barium oxalate have been grown by get method using agar-agar gel as media of growth at ambient temperature. The optimum conditions were established by varying various parameters such as concentration of gel, concentration of reactant, gel setting time etc. Prismatic platy shaped transparent crystals were obtained. The grown crystals were characterized through powder X-ray diffraction (XRD), Fourier transform infrared (FT-IR) studies, Thermogravimetric (TGA) and Differential thermal analysis (DTA). The compound crystallizes under monoclinic structure with lattice parameters a = 6.6562 angstrom
Keywords: barium oxalate; Crystal growth; FT-IR; TGA/DTA; XRD

Solubilization and conformational behavior of zein in aqueous solution of dodecyldimethylethylammonium bromide (DDAB) - Mehta, S. K.; Bhawna; Bhasin, K. K.; Kumar, Anil (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2009)
The solubilization and conformational behavior of Zein in the presence of cationic surfactant, dodecyldimethylethylammonium bromide (DDAB) have been studied. The colloidal properties of DDAB in the absence and presence of Zein have also been investigated using physico-chemical and spectroscopy methods. The surfactant appears to bind to Zein at concentrations below the critical micelle concentration (cmc) and the binding becomes weaker at concentrations above the cmc. The interaction between DDAB and Zein depends on the chemical structure and molecular parameters (conformation, molar mass, charge) of the protein. The schematic sketches of the molecular mechanisms of the complex formation between like-charged proteins and surfactants have been proposed. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Absorbance spectroscopy; Aggregation number; conductivity; DDAB; FT-IR; Surface tension; viscosity; Zein

Synthesis, characterization and effect of sintering temperature on magnetic properties of MgNi ferrite prepared by co-precipitation method - Hankare, P. P.; Jadhav, S. D.; Sankpal, U. B.; Chavan, Santosh S.; Waghmare, K. J.; Chougule, B. K. (Journal of Alloys and Compounds, 2009)
Mixed MgNi ferrites with composition Mg(0.5)Ni(0.5)Fe(2)O(4) where the mole fraction for Ni (x = 0, 0.25, 0.75, 0.5 and 1) were prepared by following co-precipitation method at temperature 110 degrees C and maintaining a pH of solution equal to 9.5 enable to achieve large particle surface area. The resultant materials obtained in powder form were sintered at different temperatures. Thermogravimetry (TGA), X-ray diffraction (XRD) and scanning electron microscopy, technique were applied to obtain structural parameters. The XRD patterns reveal the presence of(311) peak as the most intense one. The intensity of XRD peak increases with increase in sintering temperature. The saturation magnetization values showed increasing trend with increase in sintering temperature from 2.37 to 29.76 emu/g. These results along with the analysis of SEM micrographs are interpreted in terms of increase in particle grain size with increase in sintering temperature. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; Ferrites; FT-IR; scanning electron microscopy; X-ray diffraction

Biosynthesis of Se nanoparticles and its effect on UV-induced DNA damage - Prasad, Kumar Suranjit; Patel, Hirnee; Patel, Tirtha; Patel, Khusbu; Selvaraj, Kaliaperumal (Colloids and Surfaces B-Biointerfaces, 2013)
This paper reports, an environmentally benign procedure of synthesis and characterizations of selenium nanoparticles and their protective effect against UV-induced DNA damage activities. An aqueous leaf extract of lemon plant was used as a precursor for synthesis of colloidal selenium nanoparticles. Resulting nanoparticles were characterized using UV-vis spectrophotometer, photoluminescence, TEM, EDAX, FT-IR and XRD, respectively. Selenium colloidal solution exhibited an absorption maximum at 395 nm and produced an emission maximum at 525 nm. Transmission electron microscopy followed by selected area electron diffraction pattern analysis indicated the formation of spherical, polydispersed, crystalline, selenium nanoparticles of diameter ranging from (similar to 60 to 80 nm). X-ray diffraction studies showed the formation of 111, 2 0 0 and 220 planes of face-centered cubic (fcc) selenium. EDAX analysis confirmed the presence of selenium in nanosphere. Fourier transformed infrared spectroscopic investigation reveled the involvement of carboxyl (-C=0), hydroxyl (-OH), amine (-NH) functional group of lemon plant extract in preparation of selenium nano particles. MU assay as well single cell gel electrophoresis assay or comet assay revealed that synthesized selenium nanoparticles, caused less cell death of lymphocytes and prevented DNA damage, when cells were exposed to UVB. The fluorescent property of selenium nanopartides can be used as diagnostic agent. Further, their anti DNA damaging property can be investigated as a chemotherapeutic agent in cancer therapy. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Comet assay; EDAX; FT-IR; MTT assay; Selenium nanoparticles; UV-vis spectrophotometer

Synthesis and characterization of nanoporous silica SBA-15 diaminocyclohexane and its application in removal of Cu(II) and Ni(II) from aqueous solution - Sreenu, Bhogineni; Sharma, Priti; Seshaiah, Kalluru; Singh, A. P. (Desalination and Water Treatment, 2016)
A new nanoporous 1,2-diaminocyclohexane-functionalized SBA-15 (Dach@SBA-15) silica sorbent was prepared. The structure and physicochemical properties of the material were characterized by elemental analysis, X-ray diffraction, transmission electron microscopy (TEM), scanning electron microscopy, FT-IR spectroscopy, nitrogen adsorption-desorption isotherms and thermogravimetric analysis. TEM image clearly showed the sheet-like structure of Dach@SBA-15. The organic functional groups were successfully grafted onto the SBA-15 surface and the ordering of the support was not affected by the chemical modification. The Dach@SBA-15was used as a sorbent for removal of Cu(II) and Ni(II) from aqueous solution. Experimental parameters like effect of pH, contact time and metal ion concentration were studied and optimized. The adsorption isotherm data fitted well to Langmuir isotherm model and the monolayer adsorption capacity values for Cu(II) was 90.09 and for Ni (II) was 84.03 mg/g at 303 K. The experimental kinetic data fitted very well to the pseudosecond- order model. The Dach@SBA-15 could be used as a sorbent for removal of Cu(II) and Ni(II) from aqueous medium.
Keywords: Adsorption; BET; FAAS; FT-IR; Heavy metals; Nanoporous silica